THE IMPACT OF DIGITALIZATION ON MODELING THE EDUCATIONAL SPACE OF A HIGHER EDUCATION INSTITUTION - Svitlana Martynenko (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article raises the question of the impact of digitalization on the organization, conduct and modelling of the educational process in higher education institutions. It notes that the trends of digital transformation of the educational space in higher education institutions require a thorough teachers practice-oriented training aimed at the effective use of information and communication technologies in the process of professional activity. The digitalization process is presented as a convergence of digital technologies, material and social-humanitarian practices. Modelling of the educational space is interpreted as a scientifically based design that meets the set requirements and planned construction of the studied phenomenon, taking into account its features and properties. The article highlights the main conditions of digitalization of the educational space, which take into account the digital generation of children, resource support for the digitalization of education, the relevant legal framework, training of personnel potential of digital education with ICT competences, digital technologies, which are an effective mechanism for modelling the educational space. The article emphasizes the need to overcome negative processes and phenomena during the digital transformation of education, particularly: the low level of digital competences among both teachers and students; lack of a high-quality digital educational content for obtaining education; inaccessibility of scientific resources and infrastructures, etc. It also analyzes various platforms and resources (Zoom, Google Meet, Google Class and others). The article outlines the features of forming the digital educational space in higher education institutions (free search of various information in the global network; personalization, interactivity, multimedia, hyper-tempo, subculturality, etc. It also pays attention to improving the state of digital competence of participants in the educational process, which includes technical and information literacy, critical thinking, creation digital content, etc. We propose our own vision of the ways of modelling the digital educational space, the formation of professional competence in education seekers (the use of cloud technologies, mobile and Internet technologies, distance and mixed forms of education, open online courses, the development of digital libraries and campuses). The article defines the peculiarities of modelling the digital educational space in higher education institutions; proves the need to involve highly competent specialists in the process of digital educational space implementation; takes into account the main components of the educational space: the digital generation, new digital technologies, digital economy, etc.